AB0589 Subclinical atherosclerosis found both in psoriatic arthritis and rheumatoid arthritis. (23rd January 2014) - Bilgen, S. A.; Kalyoncu, U.; Kilic, L.; Karadag, O.; Canpolat, U.; Aytemir, K.; Kiraz, S.; Akdogan, A.; Kaya, B.; Ertenli, I.
Abstract : Background: Cardiovascular disease (CVD) is found in almost all chronic musculoskeletal diseases that include Psoriatic arthritis (PsA) and rheumatoid arthritis (RA). Objectives: To assess subclinical atherosclerosis in patients with PsA and RA. Methods: Patients with PsA according to classification of psoriatic arthritis (CASPAR) criteria 1 were enrolled in this cross-sectional study between June 2011 and July 2012. Demographic data (sex, age), PsA and psoriasis duration, joint pattern (monoarthritis, oligoarthritis or polyarthritis) and other PsA involvements (nail, enthesis, dactilytis) were noted. Tender joint count, swollen joint count and disease activity score (DAS)-28 were used for joint activity assessment. Erytrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were used for acute phase reactants. Last visit fasting glucose level, lipid profile (total cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL) and triglyceride), body mass index (kg/m 2 ) and blood pressure were also recorded. Conventional cardiovascular risk factors such as history of diabetes mellitus, hypertension, dyslipidemia, and smoking were noted. Sex and age matched RA and healthy controls were selected as the control group for this study. Flow mediated dilatation (FMD) and intima media thickness (IMT) were measured by a experienced cardiologist. Results: Thirty-two patients with PsA, 25 RA and 37 healthy controls were enrolled in this cross-sectional study. Psoriasis duration of PsA patients was 116±107 months. Among PsA patients, 20 (62%) patients had peripheral joint, 11 (34%) patients had axial, and 1 (3%) patient had both peripheral and axial involvement. Dactilytis 8 (25%), enthesis 10 (31%) and nail 15 (47%) were other clinical involvements. Twenty-two PsA patients (69%) and 5 (20%) of the RA patients used anti-TNF alpha treatment (p<0.001). PsA patients had lower HDL levels than RA patients (51±18 vs 65±11, p=0.006). Obesity was more frequently found in PsA patients than healthy controls [28.4±5.5 vs 24.5±4.3, p=0.002]. There were no differences in all endothelial dysfunction parameters for PsA and RA patients. However, FMD % was lower in PsA patients than healthy controls [9.4±4.8 vs 11.6±3.2, p=0.032]. Carotis IMT was more obvious in PsA patients than healthy controls [0.67±0.20 vs 0.56±0.12, p=0.01]. Endothelial dysfunction parameters were similar in patients with and without active joint lesion. Conclusions: Both PsA and RA patients have subclinical endothelial dysfunction. PsA patients had both traditional risk factors such as obesity and dyslipidemia and chronic inflammation for the develeopment of endothelial dysfunction. References: Disclosure of Interest: None Declared